The Effect of Continuous Grazing and Rest Rotational Management Systems on Grass Species Composition, Basal Cover and Production on Three Soil Types in the North West Province, South Africa - Jordaan, Franci Petra; Brits, Yvette; Rooyen, Jaco Nicolaas van (European Journal of Applied Sciences, 2023)
Rangelands represent the most extensive land cover type on Earth and many people depend on these rangelands for their livelihoods and for the ecosystem services that effect human wellbeing. The impact of grazing on community structure and ecosystem functioning is a key issue for rangeland management in order to maximize livestock production and sustainability of the operations. It is a known fact that soil differences cause differences in the palatability and utilization of grasses. Year-round continuous grazing is the management strategy used in the communal areas of the North West Province of South Africa. In this study the effect of continuous grazing and rest rotation grazing on grass species composition, basal cover and biomass production on different soil types were assessed. From the results it was clear that the effect of continuous grazing was the biggest on the andesitic soils (high clay), then the diabase soils (medium clay), whilst the effect on the quartzite soils was limited to even positive. In the rest rotation system, the effect of soil type on the different variables was negligibly small and the rangeland remained healthy and productive.